APLIKASI PELAYANAN JASA LAUNDRY PAKAIAN IDEA DENGAN MENGGUNAKAN METODE WATERFALL - Verent Agnes Wijaya; Meilyana Winda Perdana2; Jimmie, Jimmie (Kohesi: Jurnal Sains dan Teknologi, 2024)
Purpose: This research aimed to design and develop a laundry service application with in-depth needs analysis and documented. Design/methodology/approach: qualitative method Finding/result: This research produces a website application that is designed and developed for service and business needs with this application increasing operational efficiency and providing a better customer experience. Originality/value/state of the art: The difference from previous research in this study is that this application already has various features in previous studies that have not been designed and built.